(untitled) (Fiep Bulletin - online, 2015)
the study refers to soccer and leisure, in the beginning of the 20th century, in the city of Piracicaba, in the period from 1903 to 1930. It aims to raise information and data about soccer at that time, trying to identify the relationships and the social groups that occurred in the leisure and soccer areas in the Piracicaba society. Discussion: the studies were limited to analyze the main facts occurred in soccer, therefore, the first official matches in Piracicaba. The E. C. XV de Novembro de Piracicaba matches versus other teams of the region and Capital and the existent social relationships among the managers are discussion scopes of this study. Methodology and sources: it basically uses the Jornal de Piracicaba and the Gazeta Esportiva, looking for references, and also researches in Rocha Netto’s collection (2000) so as from those sources to raise possible elements to be investigated and theorized. Conclusion: the study analyzed that soccer and leisure, in the beginning of the 20th century, in Piracicaba; it did not point out differences in their social relationships players and spectators with other upcountry regions such as: Campinas, Rio Grande (RS) and Pelotas (RS). The medium bourgeoisie at that time was the one that began the practice of this sport building social relationships not for free, however soccer was not the only sport or leisure practice in the municipality, in that period.